ChemInform Abstract: Domino 6‐endo‐Dig Cyclization/Halogenation Reactions: Three‐Component Synthesis of 1, 3‐Disubstituted 4‐Haloimidazo[1, 2‐a:4, 5‐c′]dipyridines. Issue 19 (April 2016) - Enguehard‐Gueiffier, Cecile; Delaye, Pierre‐Olivier; Penichon, Melanie; Denevault‐Sabourin, Caroline; Allouchi, Hassan; Gueiffier, Alain
Abstract: The title haloimidazodipyridines are obtained by regiocontrolled one‐pot three‐step 6‐endo‐dig cyclization of ethynylimidazopyridine‐carbonitriles using Grignard reagents and iodine.